Gender and remittance flows in Viet Nam during economic transformation - Wade Don ald Pfau; Giang Thanh Long (Asia-Pacific Population Journal, 2009)
Remittances are growing in importance in our globalizing world and, consequently, they are receiving greater attention from researchers. At the microeconomic level, researchers tend to use household surveys to examine why people send remittances, how the characteristics of remittance recipients compare to those of non-recipients, how remittances impact poverty and the income distribution, if remittances are spent for consumption or investment purposes, and in order to access the role of remittances as an insurance mechanism. However, an issue that has received less attention is the role of gender in remittance decisions, from the perspective of both senders and receivers. In Viet Nam, the doi moi economic reforms that began in 1986 have led to large-scale economic transformation in the country, and gender has emerged as an important distinction for understanding how economic growth benefits society and the various subgroups of the population (Long and others, 2000). Viet Nam represents a case of transition from the traditional patriarchal social structure of Confucianism, to a structure of formal equality under socialism, and currently, with further changes taking place, to a market economy. Using the Viet Nam Living Standards Surveys (VLSSs) for 1992-1993 and 1997-1998, which include information about remittance flows at the individual level, attempts are made to shed some light on the role of gender in remittance decisions in Viet Nam during the period of rapid economic transformation.